Trainer system appliances in early treatment of malocclusions - Aleksić Ema; Lalić Maja; Milić Jasmina; Gajić Mihajlo; Milosavljević-Milovanović Mirjana; Stojanović Zdenka; Marjanović Uroš (Serbian Medical Society - Dental Section, Belgrade, 2012)
Orthodontics is dental specialty focused on preventing and treating morphological and functional irregularities of orofacial system in order to establish adequate function of mastication apparatus, good occlusion and pleasant facial appearance. It has been shown that early treatment of orthodontic anomalies during the period of children's growth is very important. The purpose of early orthodontic treatment is to eliminate or modify deviant skeletal growth and to stimulate adequate dentoalveolar and skeletal development. As known, the treatment of malocclusions should begin in primary or early mixed dentition, since the status of primary dentition has profound effect on the development of permanent dentition. Functional orthodontic appliances are most commonly used in early orthodontic treatment. The aim of this study was to describe a new prefabricated polyurethane myo-functional appliance clinically proved to be very effective.